LAVESI-FIRE simulation output at Lake Satagay, Central Yakutia, Siberia ... - Glückler, Ramesh; Kruse, Stefan (Zenodo, 2023)
Simulation output data for long-term fire-vegetation simulations with the individual-based, spatially explicit model LAVESI-FIRE. The individual, numbered simulation folders are described in the included .docx file, as well as in the related research paper (submitted). In each folder, following files can be found (_18224XX refers to the climate input used for the simulation): datatrees_currencies_18224XX.csv: Timeseries data. Simulation area-wide summarized data on tree abundance, climate, environment and fire occurrence. Each row of the table represents an individual annual simulation timestep. databiomassgrid_1_18224XX_XX00_1_X.csv: Spatial data. Each file includes tree abundance for one species (_1 = Larix gmelinii; _2 = Larix sibirica; _3 = Larix cajanderi; _4 = Picea obovata; _5 = Pinus sylvestris; _6 = Pinus sibirica), summarized in grid cells with x- and y-coordinates. datatrees_TreedensityXX00_18224XX.csv: Spatial data. Each file includes tree density, environment, and fire occurrence, summarized in ...